Co-worker support: a review of its concepts and benefits - Khairuddin, Khairun Nisa'; Omar, Zoharah (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Literatures have often focused on the importance of workplace relations between employer and employees and have focused extensively on organizational and supervisor support. Yet not much importance has been put to examine the close relationship that people develop with their co-workers and the supportive role of co-workers to employees’ well-being. Besides working with their superiors, employees share many experiences with their co-workers and there is a high possibility that employees develop a closer bond with their fellow worker compared to with their superior. Numerous studies about co-worker support have been conducted in the Asian context. However, most of the researchers adopted the definitions and instruments developed from the Western research without acknowledging our cultural differences. Therefore, this paper aims to review the literature in order to gain initial insight about the concept of co-worker support. In order to advance our understanding about the nature of co-worker support, we have formulated several fundamental questions. Specifically, the questions of who is co-worker, what does it mean by the term ‘co-worker support’ and how co-worker support influences others are crucial to be clarified. To answer these questions, we performed a preliminary analysis by reviewing previous literatures that we collected from various journal articles. By understanding the concept of co-worker support systematically, this paper will serve as a basis for future study to develop an instrument that can measure the concept as well as recognize the uniqueness of co-worker support based on the Malaysian context and its culture. Apart from exploring the concept, this study extends our knowledge about human behavior at the workplace.